2019
DOI: 10.1200/jop.19.00215
|View full text |Cite
|
Sign up to set email alerts
|

Management of Urothelial Bladder Cancer in Clinical Practice: Real-World Answers to Difficult Questions

Abstract: Management of urothelial bladder cancer has historically been challenging as a result of a limited grasp of disease biology and few available systemic therapy options, mainly consisting of platinum-based chemotherapy. Improved understanding of molecular mechanisms underlying pathogenesis of muscle-invasive bladder cancer as well as their correlation with tumor behavior and response to treatment has emerged over the past few years. Remarkable therapeutic advances have been made with the introduction of checkpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
(74 reference statements)
0
21
0
1
Order By: Relevance
“…7 Other challenges include a debate about inclusion of infiltrating immune cells or tumor cells in PD-L1 scoring, intra and intertumoral heterogeneity of PD-L1 expression, and evolution of PD-L1 status with development of treatment resistance. 17 Other predictive biomarkers are being actively investigated. TMB is an independent predictor of response to checkpoint inhibitors in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other challenges include a debate about inclusion of infiltrating immune cells or tumor cells in PD-L1 scoring, intra and intertumoral heterogeneity of PD-L1 expression, and evolution of PD-L1 status with development of treatment resistance. 17 Other predictive biomarkers are being actively investigated. TMB is an independent predictor of response to checkpoint inhibitors in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Distant metastases and lymph node involvement are correlated with poor prognosis. 26 , 27 Thus, it is critical to identify the novel therapeutic target to improve the clinical outcomes. In the current study, our data showed that ANXA8 and TUG1 were elevated, whereas miR-140-3p was downregulated in bladder cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological changes in the heart of rats after serial intravesical administration of Doxorubicin algorithms, more and more newly diagnosed cases (up to 75% according to some data) are superficial bladder cancer, when the tumor affects only the mucous membrane or submucosal layer [1]. Transurethral resection of the tumor is a common standard in the treatment of patients with superficial bladder cancer [12,22]. Intravesical chemotherapy and/or immunotherapy are used as adj uvant therapy after transurethral resection to prevent the development of residual and recurrent neoplasms [17,25].…”
Section: Reports Of Morphologymentioning
confidence: 99%